Β2SP/TET2 complex regulates gene 5hmC modification after cerebral ischemia. Issue 24 (19th November 2021) - Ma, Xiaohua; Zhang, Meng; Yan, Rui; Wu, Hainan; Yang, Bo; Miao, Zhigang
Abstract: βII spectrin (β2SP) is encoded by Sptbn1 and is involved in the regulation of various cell functions. β2SP contributes to the formation of the myelin sheath, which may be related to the mechanism of neuropathy caused by demyelination. As one of the main features of cerebral ischemia, demyelination plays a key role in the mechanism of cerebral ischemia injury. Here, we showed that β2SP levels were increased, and this molecule interacted with TET2 after ischemic injury. Furthermore, we found that the level of TET2 was decreased in the nucleus when β2SP was knocked out after oxygen and glucose deprivation (OGD), and the level of 5hmC was reduced in the OGD+β2SP KO group. In contrast, the expression of β2SP did not change in TET2 KO mice. In addition, the 5hmC sequencing results revealed that β2SP can affect the level of 5hmC, the differentially hydroxymethylated region (DhMR) mainly related with the Calcium signalling pathway, cGMP‐PKG signalling pathway, Wnt signalling pathway and Hippo signalling pathway. In summary, our results suggest that β2SP could regulate the gene 5hmC by interacted with TET2 and will become a potential therapeutic target for ischemic stroke.